2021
DOI: 10.21203/rs.3.rs-52142/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Brain in Motion II Study: Study Protocol for a Randomized Controlled Trial of an Aerobic Exercise Intervention for Older Adults at Increased Risk of Dementia

Abstract: Background: There remains no effective intervention capable of reversing most cases of dementia. Current research is focused on prevention, by addressing risk factors that are shared between cardiovascular disease and dementia (e.g., hypertension) before the cognitive, functional, and behavioural symptoms of dementia manifest. A promising preventive treatment is exercise. This study describes the methods of a randomized controlled trial (RCT) that assesses the effects of aerobic exercise and behavioural suppor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 66 publications
0
1
0
Order By: Relevance
“…The ENCORE study [18,19] demonstrated that the Dietary Approaches to Stop Hypertension (DASH) diet combined with caloric restriction and aerobic exercise conferred significant reductions in BP ($16/10 mmHg) [19], improved CVD biomarkers [18], and better cognitive functioning [20]. Although the mechanisms by which reduced BP improve cognition are not fully understood, improvements in endothelial [21,22] and cerebrovascular functioning [23,24] have both been suggested. The present ancillary study was designed to examine these additional hypotheses regarding cognitive performance in the context of the TRIUMPH trial [25], which examined the impact of a combined behavioral weight loss intervention, using aerobic exercise, caloric restriction, and the DASH diet, on cognitive function and associated mechanisms among adults with resistant hypertension.…”
Section: Introductionmentioning
confidence: 99%
“…The ENCORE study [18,19] demonstrated that the Dietary Approaches to Stop Hypertension (DASH) diet combined with caloric restriction and aerobic exercise conferred significant reductions in BP ($16/10 mmHg) [19], improved CVD biomarkers [18], and better cognitive functioning [20]. Although the mechanisms by which reduced BP improve cognition are not fully understood, improvements in endothelial [21,22] and cerebrovascular functioning [23,24] have both been suggested. The present ancillary study was designed to examine these additional hypotheses regarding cognitive performance in the context of the TRIUMPH trial [25], which examined the impact of a combined behavioral weight loss intervention, using aerobic exercise, caloric restriction, and the DASH diet, on cognitive function and associated mechanisms among adults with resistant hypertension.…”
Section: Introductionmentioning
confidence: 99%